Psychometric properties of the Questionnaire of Attitudes towards Doping in Fitness (QAD-Fit) - Tavares, Ana Sofia (2019)
Aim: The purpose of this study was to test the psychometric proprieties of the Questionnaire of Attitudes towards Doping in Fitness (QAD-Fit), originally developed by Serpa and colleagues and adapted to Portuguese gym/fitness context. Methods: A cross-sectional survey utilizing a web self-administered questionnaire was used. The sample was composed of 453 gym/fitness center practitioners, aged between sixteen and seventy-nine years old (M = 35.64; SD = 13.08), enrolled in several gym activities. Results: The confirmatory factorial analysis provided support to the four-factor structure proposed. All factors displayed good internal consistency, convergent validity, and discriminant validity. The multi-group analysis revealed cross-validity and the model´s invariance. The correlation between QAD-Fit and the Doping-related Theory of Planned Behavior Measures (DRTPBM) revealed evidence of its concurrent validity. Conclusion: The findings of this research revealed that QAD-Fit is a psychometrically valid and reliable instrument to assess attitudes towards doping consumption in gym and fitness settings.